Efficient near-infrared light-emitting diodes based on organometallic halide perovskite–poly(2-ethyl-2-oxazoline) nanocomposite thin films. Issue 47 (23rd November 2016) - Lin, Hong; Zhu, Lu; Huang, He; Reckmeier, Claas J.; Liang, Chunjun; Rogach, Andrey L.; Choy, Wallace C. H.
Abstract : Efficient near infrared perovskite light-emitting diodes are achieved by an optimized solution process that resulted in smaller sized grains, a lower bulk nonradiative recombination rate and a smoother surface of the PEtOz–perovskite nanocomposite thin film. Abstract : Organometallic halide perovskites have recently drawn considerable attention for applications in light emission diodes (LEDs). However, the small exciton binding energy of the CH3 NH3 PbI3 perovskite has the concerns of large exciton dissociation and low radiative recombination on its use in near-infrared LEDs (NIR-LEDs). Herein, we propose and demonstrate that the introduction of poly(2-ethyl-2-oxazoline) (PEtOz) into the perovskite can simultaneously improve the recombination rate and radiative decay rate for improving perovskite LED performances. Additionally, our approach results in smooth perovskite films with increased thickness, reduced roughness, and pin-hole free, which facilitates other film deposition on top for practical device fabrication, and reduces current leakage. After optimizing the perovskite–PEtOz nanocomposite emission layer in NIR-LEDs (emission peak at 760 nm), a high radiance of 12.3 W sr −1 m −2 and 70-fold enhancement of the external quantum efficiency (EQE) compared to that of the pristine perovskite case are achieved. The maximum EQE reaches 0.76%, which is the highest EQE reported so far for the CH3 NH3 PbI3 based NIR-LEDs. The simplicity of our fabrication approach combined with the outstanding device performances further highlights the enormous potential of perovskite-based LEDs.